Perilaku Konsumtif Gay di Kota Makassar - Putra, Ansar Dias; Darmayanti, Dyan Paramitha (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine: the factors that cause gays in Makassar City and consumptive behavior as a lifestyle for gays in Makassar city. In this research, qualitative research was used with a descriptive approach. Data collection techniques used observation, interviews, and documentation involving 5 (five) individual informants selected through a purposive sampling technique. The data analysis technique used is data reduction, data display, conclusion and data verification. The results of the study show that: (1) The causes of gays in Makassar City are that they want to look different, they are proud of their appearance, join in and attract the attention of others. (2) gay consumptive behavior as a lifestyle in Makassar City, there are two things: (a) it is more based on desires than needs, (b) gay consumptive behavior in Makassar city is not always related to the world of fashion, but they can also express themselves with gather with the community as an indicator of social status.